Criminal Violence Among Prisoners from a Human Rights Perspective under Law No. 22/2022 - Ariyanto Ariyanto; Dudik Djaja Sidarta; Yoyok Ucuk Suyono; Subekti Subekti; Renda Aranggraeni (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Violence among prisoners remains a significant challenge in correctional institutions and raises serious concerns regarding the protection of human rights within custodial environments. Although Indonesia has enacted Law No. 22 of 2022 concerning Corrections to strengthen the protection of prisoners’ rights, incidents of inmate violence continue to reveal gaps between normative legal guarantees and practical implementation. This study examines how the Indonesian correctional legal framework regulates prisoners’ rights and evaluates the effectiveness of existing legal mechanisms in preventing violence within correctional institutions. The research employs a qualitative normative (doctrinal) legal approach through the analysis of constitutional provisions, statutory regulations, international human rights instruments, and legal doctrines governing correctional administration and prisoners’ rights. The findings indicate that Indonesian correctional law has incorporated human rights principles consistent with international standards, including the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, and the Nelson Mandela Rules. However, several regulatory limitations persist, particularly the absence of detailed operational standards under Law No. 22 of 2022 and its implementing regulations, inadequate provisions concerning risk-based inmate classification, conflict prevention mechanisms, institutional accountability, and weak coordination among supervisory institutions. These shortcomings limit the effective implementation of human rights protection in correctional practice. Strengthening prisoners’ rights protection therefore requires doctrinal and institutional reforms through clearer derivative regulations, stronger accountability frameworks, and enhanced coordination among oversight bodies. Such reforms would improve institutional security while ensuring that correctional institutions protect human dignity and uphold prisoners’ fundamental rights